Mantoux Test in Under-five Children Visiting the out patient Child Clinic of Dr. Pirngadi Hospital, Medan - A. Razak Dalimunthe; Ridwan M. Daulay; Iskandar Z. Lubis; Helmi Muchtar Lubis; Zakaria Siregar (Indonesian Pediatric Society, 1993)
To assess the difference of Mantoux test result of under-five children who bad had BCG vaccination and those who bad not, a cross sectional study was conducted in the out patient child clinic of Dr. Pirngadi Hospital, Medan. This study was conducted from February 6, 1990 until March 3, 1990 comprising 328 under-five children (164 who bad received BCG vaccination and 164 who bad not). We found positive Mantoux tests in 86.0% of under-five children who bad BCG vaccination and 9.2% of under-five children who not bad (P<0.001). Tbe diameter of induration of Mantoux tests in the under-five children who bad received BCG at the age of 1 year or less was significantly different from those who bad received it at the age of older than 1 year (P<0.001). Positive Mantoux test with a diameter of â‰¥ 5 mm, done after 1 year or more was found in 21. 7% of children who bad BCG vaccination in the neonatal period.